A Very Rare Complication of Hyaluronic Acid Injection for Medialization Laryngoplasty: A Case With Laryngeal Abscess - ENVER, NECATİ; ASYA, ORHAN (MOSBY-ELSEVIER, 2020)
Hyaluronic acid injection for medialization laryngoplasty is a safe procedure performed on patients with glottic incompetence. Laryngeal abscess formation as a complication of injection laryngoplasty is a very rare complication, and, as we know from the literature, there has been only one case of laryngeal abscess after injection laryngoplasty in a patient with a type-I laryngeal cleft. We document for the first time a laryngeal abscess resulting from hyaluronic acid injection laryngoplasty for unilateral vocal fold paralysis. Prompt evaluation of the patient was necessary. Our patient was treated with antibiotics and corticosteroids without a need for intubation. One year after injection, the patient's Voice Handicap Index-10 score was still good and within the range of normal values.
Keywords: Injection laryngoplasty; Hyaluronic acid; Laryngeal abscess; Vocal fold paralysis; CROSS-LINKED HYALURONAN